(untitled) (Biological Sciences - PJSIR, 2010)
In the study of the effect of CaSO4 application and soaking of rice seedlings in 2% CaSO4 on N use effi- ciency of rice (var. Shaheen) in 3 sample soils (ECe=0.4, 4.8 and 8.7 dS/m, SAR=1.05, 14.86 and 21.43, pH=7.7, 8.3 and 9.20, respectively), a considerable reduction was observed in tillering (about 26% and 46%), plant height (about 20% and 46%) and yield (about 33% and 53%) of paddy grown in the saline soil (ECe=4.8 and 8.7 dS/m, respectively), as compared to the non-saline soil (ECe=0.4 dS/m), while soaking of seedlings in CaSO4 and N application with or without CaSO nutrition, significantly improved plant growth and paddy yield in all types of soil; overall, 26% increase in plant growth and 48% gain in paddy yield over the control was observed due to N and CaSO application, respec- tively, with soaking of seedlings in high salinity soil. Interestingly, seedlings soaked in 2% CaSO and with N applica- tion but with or without Ca supplementation performed statistically equal. Tissue Na+ significantly decreased, while K+ and Ca+2 concentrations were high due to N application along with Ca nutrition and soaking of seedlings in all types of soil. Maximum N uptake and apparent N recovery were detected in treatments, where N was applied supplemented with CaSO .